Structural, optical and photo catalytic properties of Cu-doped ZnO nanoparticles synthesised by co-precipitation method - Thaweesaeng, N.; Suphankij, S.; Techitdheera, W.; Pecharapa, W. (My University, 2014)
In this work, co-precipitation method was utilised to synthesise Cu-doped ZnO nanoparticles using zinc nitrate (Zn(NO3)2·6H 2O), and copper(II) nitrate trihydrate (Cu(NO3)2·3 H2O) as starting precursors for Zn and Cu sources, respectively. Structural and physical properties of as-prepared powders were examined by X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), Fourier transform infrared spectroscopy (FTIR), X-ray Photoelectron Spectroscopy (XPS) and X-ray absorption near edge spectroscopy (XANES). The XRD results reveal that Cu-doped ZnO nanopowders are in hexagonal wurtzite structure and their crystallinity deteriorates with increasing Cu doping content. FTIR results additionally show the existence of relevant chemical bonding in the samples. Meanwhile, XPS and XANES results indicate the existence of Cu ion with relevant electronic state in ZnO. Optical properties of the samples were investigated and the corresponding results suggest that Cu additive plays a crucial role in their optical properties that can be adjusted to meet the requirement for practical solar energy harvesting applications such as sun-light photocatalyst. The photocatalytic activity of as-prepared Cu-doped ZnO photocatalyst was investigated by the degradation of Rhodamine B solution. The catalyst with 6% Cu doping content exhibits the enhancement in photocatalytic activity with reaction rate of 0.0267 min-1. The significant improvement in photocatalytic activity of the doped sample may be associated to the increase of functional hydroxyl radicals due to the incorporation of specific content Cu dopant. Copyright © 2014 Inderscience Enterprises Ltd.
Keywords: Co-precipitation; Cu-doping; Photo catalytic; ZnO